Five new feather mites of the subfamily Pterodectinae (Acariformes: Astigmata: Proctophyllodidae) from passerines and hummingbirds (Aves) of Brazil - Hernandes, Fabio Akashi [UNESP]; Pedroso, Luiz Gustavo A.; Oniki-Willis, Yoshika (Magnolia Press, 2016)
Five new species of feather mites (Proctophyllodidae: Pterodectinae) are described from passerines and hummingbirds of Brazil: Amerodectes longifuscus sp. nov. from Poospiza lateralis (Nordmann, 1835) (Passeriformes: Emberizidae), A. vireonis sp. nov. from Vireo olivaceus (Linnaeus, 1766) (Passeriformes: Vireonidae), Tyrannidectes synallaxis sp. nov. from Synallaxis ruficapilla Vieillot, 1819 (Passeriformes: Furnariidae), Trochilodectes willisi sp. nov. from Phaethornis eurynome (Lesson, 1832) (Apodiformes: Trochilidae), and Xynonodectes phaethornis sp. nov. from Ph. pretrei (Lesson & Delattre, 1839) (Apodiformes: Trochilidae).
Keywords: Acari; Acariformes; Astigmata; Proctophyllodidae